The United States and the end of British colonial rule in Africa, 1941-1968 - Hubbard, James P. (James Patrick), 1945- (McFarland & Co., 2011)
"At the end of World War II, Britain possessed a vast African empire which encompassed nearly 2.7 million square miles. But by 1965, only three small African territories remained under British control. This book examines the demise of Britain's African empire, looking particularly at the role played by the United States in bringing the empire to an end"--Provided by publisher.